2004
DOI: 10.1542/peds.113.5.1321
|View full text |Cite
|
Sign up to set email alerts
|

Spanking in Early Childhood and Later Behavior Problems: A Prospective Study of Infants and Young Toddlers

Abstract: Among white non-Hispanic children but not among black and Hispanic children, spanking frequency before age 2 is significantly and positively associated with child behavior problems at school age. These findings are consistent with those reported in studies of children older than 2 years but extend these findings to children who are spanked beginning at a relatively early age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
74
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(81 citation statements)
references
References 47 publications
5
74
0
2
Order By: Relevance
“…Subsequent prospective studies yielded similar results, whether they controlled for parental age, child age, race and family structure; 12 poverty, child age, emotional support, cognitive stimulation, sex, race and the interactions among these variables; 13 or other factors. [14][15][16][17] These studies provide the strongest evidence available that physical punishment is a risk factor for child aggression and antisocial behaviour.…”
Section: The New Millennium: Addressing Causation and Broadening Focusmentioning
confidence: 96%
“…Subsequent prospective studies yielded similar results, whether they controlled for parental age, child age, race and family structure; 12 poverty, child age, emotional support, cognitive stimulation, sex, race and the interactions among these variables; 13 or other factors. [14][15][16][17] These studies provide the strongest evidence available that physical punishment is a risk factor for child aggression and antisocial behaviour.…”
Section: The New Millennium: Addressing Causation and Broadening Focusmentioning
confidence: 96%
“…Using structural equations modeling, Gunnoe and Mariner (1997) reported that spanking decreased subsequent fighting in AfricanAmerican children, but increased fighting in White children. These findings suggest the need for separate analyses by racial and ethnic differences (Slade & Wissow, 2004).…”
mentioning
confidence: 96%
“…24,25 Many studies have found a link between physical punishment and poor child and adolescent social, emotional, cognitive, developmental, and behavioral problems or impairment. [27][28][29][30][31][32][33] There is also evidence for an association between physical punishment and poor adult mental health outcomes. For example, physical punishment has been associated with depressive symptoms in US college samples.…”
mentioning
confidence: 99%